Influence of prescribed burning and/or mechanical site preparation on stand stem density and growth of Scots pine stands above the Arctic Circle : results 9-19 years after stand establishment - Sörhult, Mikael (SLU/Dept. of Forest Ecology and Management, 2012)

(untitled)
Prescribed burning was commonly used for site preparation in Sweden to establish new forests until the 1960’s, when mechanical scarification was introduced. During recent decades the interest in prescribed burnings has increased again, mainly due to certifications of forestry stating that 5% of the regeneration areas should be burned on dry and mesic soils. The objective of the study was to evaluate actual influence of prescribed burning compared to other site preparation on stand stem density, growth parameters and tree damages for Scots pine (Pinus sylvestris L.) after direct seeding and planting. The study also attempts to simulate growth until first thinning. Regeneration cost per hectare and tree was also evaluated for the different treatments. The study was performed in 2011 in Norrbotten County, above the Arctic Circle. There were four different treatments; mechanical scarification following direct seeding with or without prescribed burning and planting following prescribed burning or mechanical scarification. Stands were selected pair-wise (four pairs for each regeneration method), for each site treatment within the two regeneration methods and several criteria were used to make the pairs comparable. All stands were established about one to two decades ago. Direct seeding and mechanical scarification combined with prescribed burning showed after 9 to 16 years a significantly increased tree height and diameter in breast height compared to just mechanical scarification. The corresponding increases in stem volume, tree biomass above ground and stand stem density were as high as 210% m3sk/ha, 205% kg/ha and 43%/ha, albeit only close to significance on the 5%-level. For planting there were no clear differences in growth parameters and stand stem density between site preparations. Further, site preparation and regeneration method did not affect the degree of damage because of moose, voles and cronartium rust. The cost per established seedling today after direct seeding was only about one third of the cost for planting. To conclude, prescribed burning in combination with mechanical scarification seems clearly advantageous when direct seeding in the harsh areas above the Arctic Circle in Sweden.